(7) Diesel Exhaust Aerosol, Review Of Measurement Technology - Introduction - Bruce K. Cantrell; Winthrop F. Watts (The National Institute for Occupational Safety and Health (NIOSH))
The U.S. Bureau of Mines and others have conducted a number of occupational exposure surveys since the publication of the International Agency for Research on Cancer report of 1989(1), which labeled diesel exhaust as a probable human carcinogen. These surveys have assessed diesel exhaust exposure using measurement of diesel aerosol and/or specific polycyclic aromatic hydrocarbons as indicators of exposure. This report reviews, available diesel exhaust aerosol and gas measurement techniques. Measurement of human exposure to toxic agents is the first step in determining the exposure-dose-response relationship. It is a fundamental step in risk assessment. Measuring exposure to diesel exhaust pollutants is particularly challenging due to the complexity and variability of exhaust components. This paper reviews current occupational health standards for diesel emissions and available diesel exhaust gas and aerosol measurement techniques. Although surveys in mines have primarily assessed diesel exhaust exposure using diesel particulate matter (DPM) some exhaust gas measurements have been used as indicators of exposure. DPM is emphasized because it is a major component of diesel exhaust, is suspected to make a major contribution to the health hazard, and is measurable. OCCUPATIONAL HEALTH STANDARDS Occupational exposure surveys of diesel exhaust frequently measure regulated pollutants, or pollutants that are suspected carcinogens, even if no permissible exposure limits (PELs) have been established. In the United States, various organizations recommend a range of allowable values for diesel exhaust gaseous constituents, including carbon monoxide (CO), carbon dioxide (CO2), sulfur dioxide (SO.), nitrogen dioxide (NO2), nitric oxide (NO), and formaldehyde (HCHO). Table I summarizes these recommended levels, showing 8-hour or 10-hour time-weighted-average values where available; where these are not available, 15-minute short-term [ ]